Diagnosis, Diagnosis Differensial dan Penatalaksanaan Immunosupresif dan Terapi Sumsum Tulang pada Pasien Anemia Aplastik - .., Thaha; Lestari, AA Wiradewi; Sutirta Yasa, I Wayan Putu (E-Jurnal Medika Udayana; vol 3 no 2 (2014):e-jurnal medika udayana, 2014)
Anemia aplastic is anemia with bone marrow failure characterized by pancytopenia and at the most case with hypoplasia bone marrow. The incidence of anemia aplastic is 3 -6 case per 1 million persons per year. Clinical presentations of anemia aplastic are anemia syndrome, leukopenia will cause infection, and thrombocytopenia will cause bleeding. Diagnosis of anemia aplastic is based on bicytopenia and pancytopenia without malignancy, infiltration, and suppression to bone marrow. Treatments for anemia plastic are main therapy, supportive therapy and long-term therapy. Main therapy is avoiding the caustic agent. Supportive therapy gives when there is a symptom from anemia, neutropenia and thrombocytopenia. Long-term therapy is immunosuppressive therapy and bone marrow therapy.
Keywords: anemia, anemia aplastic, pancytopenia